Poverty and Agricultural Productivity Growth Nexus in the Non-Plantation Agriculture in Sri Lanka - Herath, H.M.W.A. (Journal of Social and Development Sciences, 2018)
Not only there is a close relationship between poverty and agriculture productivity but also agriculture is considered as a significant means of plummeting poverty in the long-term and in the shortterm. While agriculture may not be central as the driver of economic growth in current global neo-liberal economic context it is generally accepted that the food security and livelihood development aspects for all still warrants developing agriculture, a situation that holds true for Sri Lanka too. Productivity in agriculture is determined by conditions in both the natural, socioeconomic and community factors. The productivity in the country’s agriculture sector is rooted in the farming system, namely, the farm and the farmer/farm operator. These two units are in an interacting whole which makes property of one a quality of another. Small plot size, the existing tenure system, low levels of education and skills of farm operators and behavior of two patrons (government and traders) in the sector are the major backward determinants affecting to place in the farmer into a vicious cycle of poverty. This background does not help to generate a dynamic, risk bearing and enterprising farmers for the economy and this leads to low productivity and then the continuation of poverty of farmers. The lack of attentiveness of overall situation and lack of holistic approach to problems providing appropriate solutions to individuals are constraints in agriculture development. Solution is the hallmark of policies and interventions in agriculture. Present focus is also on subsistence-based model and the approach is piecemeal.